ANÁLISE DE CUSTO-BENEFICIOS DO USO DE ANÁLOGOS DE GNRH NA DESOVA INDUZIDA DE LAMBARI-DE-RABO-AMARELO - ALMEIDA, Mizael Pereira; SIMÕES, André Rozemberg Peixoto; CAITANO, Welisson Aparecido Bispo; TAVARES, Tainara Viera; COSTA, Deliane Cristina; WANDERLEY, Alysson Martins (ANAIS DO ENIC, 2025)
-